2018
DOI: 10.1097/ccm.0000000000002946
|View full text |Cite
|
Sign up to set email alerts
|

How Do You Feel? Subjective Perception of Recovery as a Reliable Surrogate of Cognitive and Functional Outcome in Cardiac Arrest Survivors

Abstract: Long-term subjective and objective outcome appears good in the majority of cardiac arrest survivors. Specific functional and cognitive impairments were found in patients reporting unsatisfactory recovery. Subjective recovery was strongly correlated with objective assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 32 publications
3
23
0
8
Order By: Relevance
“…that those with excellent recovery may be more likely to say yes to being part of the study, skewing the data in a positive way. These tendencies have been observed in other studies [10,12,17]. On the other hand, we have information from the main TTM2-trial on the patients declining to participate in this sub-study, facilitating analyses of missing data.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…that those with excellent recovery may be more likely to say yes to being part of the study, skewing the data in a positive way. These tendencies have been observed in other studies [10,12,17]. On the other hand, we have information from the main TTM2-trial on the patients declining to participate in this sub-study, facilitating analyses of missing data.…”
Section: Discussionsupporting
confidence: 67%
“…Striving for high specificity, especially in the neuropsychological test battery, we adjust for level of education in our main outcome measures. When comparing the results on the neurocognitive screening with the detailed neuropsychological test battery, the chosen cut-score of z ≤ − 1.65 was inspired by a similar OHCA study [12]. We have refrained from pre-specified comparisons of the neuropsychological function between the 33°C and normothermia treatment arms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…medication nonadherence, lifestyle, and rehabilitation noncompliance) [35,38,39], which can ultimately lead to a worse perceived and actual recovery. Due to low rates of depression in Juan et al [9], their study could not assess the effect of depressive symptoms on recovery perceptions. Overall, our findings support the notion that, when present, depressive symptomatology holds greater importance in cardiac patients' perceived recovery compared to other recovery domains.…”
Section: Discussionmentioning
confidence: 94%
“…For example, Steinbusch et al [8] found that post-arrest patients' perceived cognitive impairments were not indicative of their actual cognitive impairments at 3-and 12-month follow-ups. On the contrary, Juan et al [9] found post-arrest patients' cognitive impairments, but not depressive symptoms, to be strongly correlated with negative perceptions of recovery at 6-months; however, the incidence of depression in that cohort was low (6%), and the relatively small sample size (n=50) precluded definitive conclusions. In samples of stroke survivors and older adults, subjects' cognitive complaints were correlated with emotional well-being and depressive symptoms, rather than objective measures of cognitive impairment [10,11].…”
Section: Introductionmentioning
confidence: 83%